Strategies for the double production season in the Peruvian Andean Region - Quispe Rodriguez, Juan (2020)
The double production season in agriculture, in other words, is to obtain two harvests in one year, the same that is important to consider in an efficient and profitable agriculture, so it is important that the agri-food sector must adapt to the pace of competitiveness necessary to become true market-oriented production centers with fair prices, improving management models, process control to facilitate decision making and incorporate technological advances; In many places irrigation projects have been carried out to facilitate the proper use and management of irrigation water; however, many of them do not consider the very important aspect of "agricultural development", which is the decisive activity for evaluating the impact of the project and which will ultimately justify the investment made when farmers improve their income through better organization, application of technologies, negotiation capacity and greater profitability of their products, and consequently improve their standard of living and quality of life. This document presents the research work carried out in the Mantaro Valley and other areas of the Junin region - Peru, with good results considering crops tolerant to low temperatures, early and with good profitability, efficient use of irrigation water and also proposes a basic crop table that can be considered for other inter-Andean areas.